E-Finance : Mitigation of Fraud Tendency in Indonesia - Imanita Septian Rusdianti; Ririn Irmadariyani; Alwan Sri Kustono (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This research aims to determine the application of e-finance in the Lumajang Regency DPUTR and its role in improving internal control and mitigating fraud risk with fraud diamond theory analysis. Design/methodology/approach: This research is qualitative case study research with descriptive methods. Data collection techniques use observation, documentation and semi-structured in-depth interviews. Findings: Data analysis techniques through the stages of plan, design, prepare, collect, analyze, share. The results of this study include: 1) The application of e-finance in the Lumajang Regency DPUTR based on realtime online which is integrated with all LUMAJANG REGENCY OPDs to facilitate financial reporting in accordance with public sector accounting rules to prevent fraud so as to create transparency and can be accounted for; 2) Based on diamond theory fraud analysis, the application of e-finance is able to mitigate risks. fraud; 3) E-finance plays an important role in improving the internal control of the Lumajang Regency DPUTR. Research limitations/implications: The limitation of this research is the lack of theoretical foundations and previous research on the application of e-finance in public sector organizations. This finding provides solutions to public sector organizations in minimizing fraud through the application of e-finance applications by using fraud diamond theory analysis. Practical implications: This study adds literature on the application of e-finance to public sector organizations and its role in mitigating the risk of fraud which has not been discussed in previous studies. Originality/value: This paper is original. Paper type: Research paper